EFL teachers look at themselves : could they grow together? (2001)
ABSTRACT:This paper reports the findings of a study in which EFL teachers reflect on their work condictions and professional needs. Data were collected throung focus groups. Results show that EFL teachers from public and private schools see themselves as very different from each other. The language proficiency the believe each group has, the access to teaching materials, the students’ motivation, the social problems faced in their classrooms, and the work conditions represent the issues that generate the división between these two groups. The need to promote more instances of mutual recognition and understanding in professional training programs is concluted by the researchers.